Organización Contable en Almacenes Promacon de la ciudad de Loja, periodo del 01 de abril al 30 de junio del 2022. - Contento Puga, Stefany Alejandra (2023)
The present titling work called ACCOUNTING ORGANIZATION IN PROMACON STORES OF THE CITY OF LOJA, PERIOD FROM APRIL 1 TO JUNE 30, 2022, began with the purpose of providing the owner with truthful, real and timely information about the economic situation and of the business for the correct decision making, in addition to fulfilling as a prerequisite to obtain the title of Engineer in Accounting and Auditing CPA. In order to comply with the proposed objectives, an analysis of the nature, scope and business of the warehouse was carried out, which facilitated the design of the plan and manual of accounts according to the needs of the company, with its respective coding and description detailing all the accounts. of the assets, liabilities, equity, costs, expenses and income, the preparation of the initial inventory continued through the physical verification of all the values, goods, rights and obligations that the store has, determining a total asset of $98.615,63, a total liabilities of $16.302,01, and its equity of $82.313,62, giving rise to the Initial Statement of Position. The control of the movement of the Merchandise account was carried out through the Multiple Account System or Periodic Inventory, obtaining detailed information for the regulation of the merchandise account at the end of the year. Finally, the accounting process was developed based on the collection of source documentation and other information that supports the savings made by the warehouse, facilitating its registration in the auxiliary books previously prepared, whose summary was published in the daily book, and then transferred to the general ledger, structuring the Trial Balance based on the balances obtained, the Work Sheet with the respective adjustments and regulation seats and obtaining the Financial Statements, where the Income Statement extracted a total income of $48.954,00, a total of expenses of $9.191,68 showing a profit in the period from April 1 to June 30, 2022, of $21.841,74, the Statement of Financial Position that reflects an asset of $119.087,83, a liability of $14.932,48 and a patrimony of $82.313,62, finally the movements of the cash and bank account are reflected in the Cash Flow Statement. These results obtained obtained significant information to the owner for the correct decision making and the good use of all the resources.